Fighting China's hackers. (Economist, 2013)
The article focuses on China-based computer hackers' efforts to steal intellectual properties (IP) of U.S. business enterprises as of May 25, 2013, discussing why many victimized companies have been reluctant to alienate Chinese markets by retaliating.